Supervision bases on learning as a competitive advantage - Solf Zárate, Arturo (2008)
This paper introduces a proposal for allowing labor organizations to achieve a competitive advantage in enhancing their workers´learning, for which supervisors should play a principal roles, in providing conditions stimulating a continuous learning. The kind of learning emphasized is the one informally acquired, unlike formal procedures of traditional training. Finally, there are two questionnaires on the supervisor´s made as a learning  facilitator, which might be used in labor training programs.